2018
DOI: 10.1155/2018/1638462
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Development of Vaccines for Diabetes, Hypertension, and Atherosclerosis

Abstract: Vaccines are commonly used in the prevention of infectious diseases. The basic principle of vaccination is to use specific antigens, endogenous or exogenous to stimulate immunity against the specific antigens or cells producing them. Autoantigen or oligo vaccination has been used for disease animal models. More recently humanized monoclonal antibodies have been successfully used for the treatment of neoplastic disorders or familial hypercholesterolemia. Humanized monoclonal antibody therapy needs repeated inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 87 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…This widespread issue can be resolved with a vaccine exerting long-term effects [ 258 , 259 ]. Antigen-specific immunoprotection via vaccination is a recent potential approach to prevention and treatment of chronic diseases [ 260 ]. Mechanisms include the production of antibodies, T-cell anergy, and the induction of regulatory T cells [ 261 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…This widespread issue can be resolved with a vaccine exerting long-term effects [ 258 , 259 ]. Antigen-specific immunoprotection via vaccination is a recent potential approach to prevention and treatment of chronic diseases [ 260 ]. Mechanisms include the production of antibodies, T-cell anergy, and the induction of regulatory T cells [ 261 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Endogenous proteins may promote the hypercreativity and autoimmune reactions, however few studies showed that predicted epitopes of endogenous proteins exhibited significant, safe and effective results in animals. Recently, the vaccines for metabolic diseases have made considerable progress, particularly in the treatment of dyslipidemia, atherosclerosis, diabetes mellitus and hypertension, but comprehensive studies are required before any clinical applications [70]. Since T2DM is a multifactorial disorder, T2DM therapeutic-vaccine has been designed to predict obesity protein antigens [71].…”
Section: Discussionmentioning
confidence: 99%
“…In China, the hypertension disease burden is increasing [ 210 ]. Based on the basic principle of vaccination, researchers began to develop therapeutic vaccines to control hypertension, such as ATR12181, pHAV-4Ang IIs, CYT006-AngQb, AngI-R, PMD3117 and ATRQβ-001 [ 211 ]. Downham et al designed a vaccine, named “PMD-3117”, targeting angiotensin I, that is composed of an analog of angiotensin I fused to KLH and aluminum hydroxide adjuvant.…”
Section: Therapeutic Vaccines Against Noncommunicable Diseasesmentioning
confidence: 99%